2005
DOI: 10.4049/jimmunol.175.8.4981
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hypotonicity-Induced Calcium Signaling and Integrin Activation by Arachidonic Acid-Derived Inflammatory Mediators in B Cells

Abstract: We previously characterized the initial steps in the activation of novel (calcium-permeant) nonselective cation channels (NSCCs) and calcium release-activated calcium channels in primary murine B lymphocytes. Phospholipase C products, namely diacylglycerol and d-myo-inositol 1,4,5-trisphosphate, were identified as proximal intracellular agonists of these respective channels following mechanical stimulation of B cells. However, neither the distal steps in NSCC activation nor the contribution of these channels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…The AA-induced K + current could not be found in these studies because they used Cs-methanesulfonate pipette solution for the wholecell patch clamp experiments [21,41]. Partly consistent with these papers, AA-activated cationic conductance was also found in mouse B cell lines (Fig.…”
Section: Aa-induced Membrane Potential Changes and Ca 2+ Signal In B supporting
confidence: 67%
See 2 more Smart Citations
“…The AA-induced K + current could not be found in these studies because they used Cs-methanesulfonate pipette solution for the wholecell patch clamp experiments [21,41]. Partly consistent with these papers, AA-activated cationic conductance was also found in mouse B cell lines (Fig.…”
Section: Aa-induced Membrane Potential Changes and Ca 2+ Signal In B supporting
confidence: 67%
“…Therefore, persistent K + efflux and strong hyperpolarization by AA might play a role in the PLA 2 -dependent apoptosis of immature B cells. However, apart from the autologous generation by PLA 2 intrinsic to immature B cells, AA can be released from inflammatory tissues and splenic B cells under mechanical stimuli [41]. In this study, we found that LK bg and their activation by AA are often observed in the B220 + /AA4.1 + subset of splenic B cells (immature B cells) whereas not in the B220 + /AA4.1 − subgroup (mature B cells, Fig.…”
Section: Aa-induced Membrane Potential Changes and Ca 2+ Signal In B mentioning
confidence: 71%
See 1 more Smart Citation
“…Other channels potentially found in B cells include other TRPC members, various members of the transient receptor potential-vanilloid receptor-1-related (TRPV) family 88,89 , TRPM2 and TRPM7 [90][91][92] , and undefined stretch-activated ion channels and eicosanoid-activated channels [93][94][95] . In addition, convincing evidence for expression of mRNA for splice variants of α-subunits of classic voltage-operated Ca 2+ channels has been reported in B cells and T cells, although electrophysiological evidence of voltage-operated Ca 2+ currents is lacking, suggesting that these splice variants may not be voltage-operated, but instead must have alternative gating mechanisms [96][97][98] .…”
Section: Ca 2+ Entry Through Non-soce Mechanismsmentioning
confidence: 99%
“…A higher level of 20-HETE promotes inflammation by the production of Reactive Oxygen Species (ROS) and Nuclear Factor kappa-B (NF-kB) in the cerebral vasculature [66]. It also increases cytokines production and expression of adhesion molecules Intercellular Adhesion Molecule 1 (ICAM-1) and Vascular Cell Adhesion Protein 1 (VCAM-1) on B-lymphocytes [67,68] and endothelial cells [69,70] which further promotes margination of macrophages and enhancing inflammatory cascade. Functional genetic variants in CYP4F2 and CYP4A11 that decrease the formation of 20-HETE are linked to hypertension [71,72] and stroke [19,20,73].…”
Section: Genes Contributing To Cerebral Autoregulationmentioning
confidence: 99%